2015
DOI: 10.1158/0008-5472.can-15-0378
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Receptor Promotes Skin Tumor Formation by Preventing Epithelial Cell Activation of Notch1

Abstract: The urokinase-type plasminogen activator receptor (uPAR) has a well-established role in cancer progression, but it has been little studied at earlier stages of cancer initiation. Here, we show that uPAR deficiency in the mouse dramatically reduces susceptibility to the classical two-stage protocol of inflammatory skin carcinogenesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
2
4
0
2
Order By: Relevance
“…These data were confirmed clinically: it was found that human differentiated keratoacanthomas expressed low levels of uPAR [47].…”
Section: Discussionsupporting
confidence: 55%
“…These data were confirmed clinically: it was found that human differentiated keratoacanthomas expressed low levels of uPAR [47].…”
Section: Discussionsupporting
confidence: 55%
“…Urokinase-type plasminogen activator receptor (uPAR) is a component of the plasminogen activator (PA) system. This system plays an important role in many physiological and pathological processes, including tissue remodelling [ 8 ], thrombosis [ 9 ], inflammation [ 10 ], and tumourigenesis [ 11 ]. The soluble form of uPAR (suPAR) can be detected in serum and other organic fluids [ 12 ]; its levels are increased in patients with HIV infection, malaria, tuberculosis, and sepsis, suggesting that it could serve as a useful prognostic biomarker [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…uPAR partitioning to lipid rafts contributes to regulate some biological activities. For example, in basal kerantinocytes, uPAR may sequester the TNF-α converting enzyme (TACE) within lipid rafts, preventing Notch1 activation, and thereby promoting cell proliferation and tumor formation [20]. In endothelial colony-forming cells (ECFCs), inhibition of uPAR expression by antisense oligonucleotides promotes disruption of caveolin-containing lipid rafts, suggesting a prominent role for uPAR in caveolae organization [21].…”
Section: Discussionmentioning
confidence: 99%